1. −(5 + 2) + {−15 + 2 − [−10 + 2 − (5 − 2)] + 10}
-7+{-13-(-8-3)+10} = -7-13+11+10 = 1
2. 15(3𝑥 − 2) − 7(2𝑥 − 1)
45x-30-14x+7 = 31x -23
3. 10𝑚 + (2𝑚 − 5𝑛𝑝) + 𝑛𝑝
10m + 2m - 5np + np = 12m-4np
4. 15(9 − 2) + 7(6 − 1) − [7(6 + 3) − 4(3 − 1)]
105 + 35 - [ 63-8 ]
140-55 = 85
5. 15(12 − 2) − 7(8 − 1)
150-49 = 101
6. 7(2𝑥 + 3) − 4(𝑥 − 1)
14x+21-4x+4 = 10x + 25
7. 15(3𝑥 − 2) + 7(2𝑥 − 1) − [7(2𝑥 + 3) − 4(𝑥 − 1)]
45x - 30 + 14x -7 - [ 14x +21-4x +4 ] =
59x - 37 -14x - 21 + 4x - 4 = 49x -62
8. 30 − {(2 + 7) + 4 − [2 + (6 + 4) − 6]}
30 - {13 - 6 } =
30 - 7 = 23
9. 20 − {[23 − 2(5 ∙ 2)] +( 15/3 ) − 6}
20 - {3 + (-1)} = 18
10. −(𝑎 + 𝑏) + {−3𝑎 + 𝑏 − [−2𝑎 + 𝑏 − (𝑎 − 𝑏)] + 2𝑎}
- a - b + { -3a + b - [- 2a + b - a + b] + 2a} =
-a -b + { - 3a + b + 3a - 2b + 2a } =
- a - b + 2a -b = a-2b
No hay comentarios:
Publicar un comentario